1999
DOI: 10.1175/1520-0493(1999)127<1005:iaivim>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Interannual and Intraseasonal Variations in Monsoon Depressions and Their Westward-Propagating Predecessors

Abstract: The majority of monsoon depressions develop from the regenesis of westward-propagating residual lows from the east. Most of these residual lows can be traced to weather disturbances in the south China Sea, including tropical cyclones and 12-24-day monsoon lows. Hypothetically, any mechanism causing a variation in the occurrence frequency of these two types of weather disturbances in the western tropical Pacific-south China Sea (WTP-SCS) region may result in a corresponding change in the formation frequency of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
90
0
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(98 citation statements)
references
References 23 publications
5
90
0
3
Order By: Relevance
“…In contrast, during the inactive phases of intraseasonal variation, the westerly regions spread around the latitude of 20°N near 10 August 1996, which would disturb the westward movement of WD through the path over the Indochina Peninsula, Typhoon MARTY being examples. The similar relations between the frequency of WDs and the intraseasonal variation of monsoon trough in P2 are found in the other years as suggested by Chen and Weng [1999].…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…In contrast, during the inactive phases of intraseasonal variation, the westerly regions spread around the latitude of 20°N near 10 August 1996, which would disturb the westward movement of WD through the path over the Indochina Peninsula, Typhoon MARTY being examples. The similar relations between the frequency of WDs and the intraseasonal variation of monsoon trough in P2 are found in the other years as suggested by Chen and Weng [1999].…”
Section: Resultssupporting
confidence: 85%
“…Statistical analysis by Chen and Weng [1999] indicated that about 60% of monsoon depressions in summer from June to August was related to the WDs that could be traced to typhoons in the WNP-SCS.…”
Section: Introductionmentioning
confidence: 99%
“…As discussed by Hartmann et al (1992), Schnadt et al (1998), Heta (1990), and Chen and Weng (1999), the relationship between the occurrence of tropical cyclones and this higherfrequency intraseasonal oscillation in the tropics is an important subject for future research. Furthermore, the interaction between high frequency eddies and the MJO will be demonstrated in the future, as was done with the Northern Hemisphere winter case by Matthews and Kiladis (1999a).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Tropical-extratropical interactions on submonthly timescales and the roles of the interactions in tropical and subtropical variability during the NH summer over the Pacific basin have not been studied in depth. A summertime extreme of convective activity in this frequency range occurs over the western tropical Pacific region including the South China Sea (e.g., Chen and Chen 1995;Vincent et al 1998;Kiladis 1998). Our study examines how this convection is triggered and the impact that it has on large-scale circulation.…”
Section: Introductionmentioning
confidence: 99%
“…tropical cyclones, perturbations, and monsoon lows) over the SCS by short wave train anomalies emanating from the western tropical Pacific (Saha et al, 1981;Chen and Weng, 1999;Chen and Yoon, 2000) and (2) an east-west inter-annual seesaw response to the tropical Pacific sea-surface temperature (SST) anomalies, the so-called Walker circulation for the Indo-Pacific inter-annual interaction (Chen and Yoon, 2000). The SASM rainfall over the Indochina Peninsula can be interpreted as a result of northward seasonal rain belt migration, in an east-west oriented precipitation belt called the inter-tropical convergence zone (ITCZ), over the equatorial Indian Ocean in the Boreal summer.…”
Section: Introductionmentioning
confidence: 99%